Can host countries have legitimate expectations? - Karl P. Sauvant; Güneş Ünüvar (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2016)
In international investment law, foreign investors can claim that host countries have acted against investors' legitimate expectations. Especially in light of recent investment treaties recognizing sustainable development goals and the importance of responsible business conduct, this Perspective asks whether host countries too can have legitimate expectations regarding foreign investors' conduct.
Keywords: 330